FRANSUZ TILIDA RANGLARNI NOMINATSIYA QILISH VA ULARDAN FOYDALANISH XUSUSIYATLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article is devoted to the study of ways to display color using adjectives in French. The research material consisted of 90 names of color shades, obtained through a continuous sampling from dictionaries and Internet sources. The names of such specific color shades are given based on the association with the color of various objects, events and substances that have a similar shade. The units studied in the article are classified according to the type of metaphorical transfer based on nomenclature.
Keywords: color, denomination, pattern, association, natural phenomena.